Caveat Emptor: Higher Education Rankings as Profit Centers - Hazelkorn, Ellen; Altbach, Philip (International Higher Education, 2024)
<h3 id="global-higher-education-rankings-have-become-a-multifaceted-and-highly-profitable-enterprise-the-three-main-rankingstimes-higher-education-the-qs-and-the-academic-rankings-of-world-universities-shanghai-rankingsoffer-consulting-services-big-data-analysis-benchmarking-and-other-services-questions-concerning-conflict-of-interest-and-ethics-of-the-system-must-be-raised" data-pm-slice="1 1 []">Global higher education rankings have become a multifaceted and highly profitable enterprise. The three main rankings—Times Higher Education (THE), QS, and the Academic Rankings of World Universities (Shanghai rankings)—offer consulting services, big data analysis, benchmarking, and other services. Questions concerning conflict of interest and ethics of the system must be raised.